Analysis of the Impact of Financial Literacy on Millennial Investment Behavior in the Digital Era - Nas, Arham Bin Irham; Iksanudin, Udin; Poetri, Iin Priany (Universitas Sains dan Teknologi Komputer, 2025)
The rise of digital technology has influenced Indonesian millennials' financial behavior, especially in digital investment. However, wider access to financial products is not matched with adequate understanding, often leading to impulsive decisions. This highlights the gap between financial inclusion and financial literacy, making it crucial to study how literacy affects investment behavior in the digital era. This research examines how millennial financial literacy impacts investment behavior and how the digital environment moderates this effect. A quantitative method was used with data from 200 millennials engaged in digital investment, collected through an online questionnaire. Data were analyzed using multiple linear regression and moderated regression analysis (MRA). Results show that financial literacy significantly and positively influences investment behavior (p < 0.001). Moreover, the digital era strengthens this effect—active use of fintech and online communities amplifies the impact of financial literacy on rational investment choices. Financial literacy, investment behavior, and digital factors are interlinked. The study's findings are valuable for developing digital-based financial education and designing investment platforms that both guide and align with millennial traits.